MOTIVASI INDONESIA BERGABUNG DALAM ICCO (INTERNATIONAL COCOA ORGANIZATION) TAHUN 2012 - Danu Oktriando; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research explains Indonesia’s decision to participate in International Cocoa Organization (ICCO) membership. A policy base on the national interest of Indonesian, one of which agenda National Medium-Term Development Plan (RPJMN) about revitalization farm program. That focuses on three major commodity. One of which is cocoa farm.To analyze the problem in this research, this research used the nation-state level of analysis, the level of analysis to concentration on state and how the state decides to take policy that based on national interests. Perspective that used in this study is liberal, its used to discuss why is Indonesia want to join in the International Cocoa Organization (ICCO) and foreign policy theory to discuss the policy of Indonesia to ratification membership status on ICCO.KeyWords: ICCO, Policy, Cocoa Farm, Comparative Advantage.